2011
DOI: 10.1007/s12011-011-9109-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Selenium, Zinc, Copper and Lipid Levels in Postmenopausal Turkish Women and Their Relation with Osteoporosis

Abstract: It has been shown that the trace elements and lipids play role in the growth, development and maintenance of bones. We aimed to investigate serum selenium (Se), zinc (Zn), copper (Cu) and lipid (total cholesterol, triglyceride (TG), high density lipoprotein-cholesterol, low-density lipoprotein-cholesterol) levels in postmenopausal women with osteoporosis, osteopenia and in healthy controls, and to determine the relationship between Se, Zn, Cu and lipid parameters and bone mineral density (BMD). The study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 63 publications
3
43
2
Order By: Relevance
“…While Buizert et al [28] observed inverse association between QUS and HDL-C. We only found TG was positively associated with QUI in postmenopausal women, consistent with study in Turkey [29]. Some other studies suggest a certain relation between LDL-C and QUS which was not discovered by us.…”
Section: Discussionsupporting
confidence: 89%
“…While Buizert et al [28] observed inverse association between QUS and HDL-C. We only found TG was positively associated with QUI in postmenopausal women, consistent with study in Turkey [29]. Some other studies suggest a certain relation between LDL-C and QUS which was not discovered by us.…”
Section: Discussionsupporting
confidence: 89%
“…In serum level analysis, copper concentration, unlike calcium, does not show correlation with degenerative disc disease [30]. Also it does not show correlation with osteopenia or osteoporosis in postmenopausal women [31,32]. …”
Section: Resultsmentioning
confidence: 99%
“…In clinical observations, selenium status was negatively related to bone remodeling and positively to bone density in healthy postmenopausal women [ 50 ]. However, a comparable study by Arikan et al [ 51 ] did not find any correlation between serum selenium and bone mass in a small group of postmenopausal women. Thus, further investigation is needed to clarify the importance of selenium for bone health.…”
Section: Selenium May Also Have Beneficial Effects On Bone Homeostasimentioning
confidence: 89%